(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the status of receiving education on rational drug use, the criteria in medical drug selection, and the level of knowledge of dentists working in a dentistry faculty in Turkey. Materials and Methods: This was a descriptive study based on a questionnaire. One hundred seventeen (74%) dentists volunteered to participate in the study. The questionnaire consisted of 20 questions investigating sociodemographic features and rational drug use. Results: The mean age of the dentists was 30.8±7.2 years, and 62.4% of them were men. The mean period of professional experience was 8.9±7.1 years. The most frequently used resources of references while prescribing medicine were Vademecum (medical drug guide) (61.5%), the internet (59.0%), and colleagues (49.6%).According to the responses of the dentists about their level of knowledge of drugs, the most frequently reported condition described as ‘good’ was drug indications (43.6%). The dentists had a moderate level of information about posology and administration route (48.7%), pharmacologic features (48.7%) and contraindications (46.2%). The number of dentists who stated that they considered the cost while prescribing was low (always, 6%, and frequently, 15.4%). 23.9% of the dentists received education for rational drug use. Conclusion: It was determined that dentists did not receive adequate and effective education on rational use of drugs. Regular and continuous education before and after graduation is a necessity for both dentists and their patients.